Dynamic Response of a Cracked Composite Beam subjected to moving Load - Hussein, Nazhad Ahmad (Anbar Journal of Engineering Sciences, 2019)
The forced deflections of simply supported cracked composite beams are investigated when subjectedto moving dynamic load. The crack is modeled as rotational spring and used in the formulationof the composite beam with a moving load in sinusoid wave. The numerical solution issatisfactory compared to the experimental results. The effects of crack depth and crack positionsat different load speed are studied. The results show that the forced deflection increased withincreasing the speed ratio and crack depth.